Evaluasi Laman Penerimaan Mahasiswa Baru dengan WebQual 4.0 dan Importance-Performance Analysis - Aditya Gusti Mandala Putra; Dinan Yulianto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
An evaluation of the website quality must be considered on an ongoing basis by an institution because the website quality is part of the institution’s image in cyberspace. As a higher education institution, Universitas Ahmad Dahlan (UAD) utilizes the website in the new student admission (NSA) process. Referring to the initial review process using a Blackbox method, it was found that the UAD NSA website had a function that was not working properly. It was also identified that the information content of the registration process displayed was incomplete. This study aims to determine the quality of the UAD NSA website based on the interpretation of the end-users with instruments adopted from the WebQual 4.0 method including usability quality, information quality, and service interaction quality variables. The evaluation process began with the instrument testing which included validity and reliability testing. The process of WebQual 4.0 statistical test was carried out through classical assumption testing which included normality, autocorrelation, multicollinearity, heteroscedasticity testing, t-test, and f-test. The final evaluation process was an importance-performance analysis (IPA) test with the level of conformity, gap, and quadrant analysis between performance and expectations. The results of testing the validity and reliability of 23 instrument items by 100 respondents got an overall value of rtable greater than the value of rcount, which was 0.195, and Cronbach’s alpha value was greater than 0.6 so that the research instrument was valid and reliable. The results of the test involving 250 respondents obtained WebQual 4.0 statistical results, each independent variable (A) partially and simultaneously correlated with the dependent variable (B). The results of the IPA quadrant test indicates that the A2.5 variable related to providing easy-to-understand information needs to be optimized by NSA and web service managers at UAD.